Solving Fractional Difference Equations Using the Laplace Transform Method - Li Xiao-yan; Jiang Wei (Abstract and Applied Analysis)
We discuss the Laplace transform of the Caputo fractional difference and the fractional discrete Mittag-Leffer functions. On these bases, linear and nonlinear fractional initial value problems are solved by the Laplace transform method.